Qaybta daaqsinka Arda-Oola - International Livestock Research Institute (International Livestock Research Institute, 2024)
A community rangeland management plan for the Arda Olla rangeland management unit, as a step in participatory rangeland management being implemented by the HEAL project and the CGIAR Science Program on Multifunctional Landscapes